2023
DOI: 10.3390/math11183982
|View full text |Cite
|
Sign up to set email alerts
|

On the Cryptanalysis of a Simplified AES Using a Hybrid Binary Grey Wolf Optimization

Rizk M. Rizk-Allah,
Hatem Abdulkader,
Samah S. Abd Elatif
et al.

Abstract: Cryptosystem cryptanalysis is regarded as an NP-Hard task in modern cryptography. Due to block ciphers that are part of a modern cipher and have nonlinearity and low autocorrelation in their structure, traditional techniques and brute-force attacks suffer from breaking the key presented in traditional techniques, and brute-force attacks against modern cipher S-AES (simplified-advanced encryption standard) are complex. Thus, developing robust and reliable optimization with high searching capability is essential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Further, applying quantum cryptanalysis to block ciphers such as S-DES and S-AES signifies a major advancement, leveraging quantum computing's superior processing capabilities to enhance cryptanalytic efficiency. Rizk-Allah et al [35] demonstrated the power of hybrid algorithms, combining classical and natureinspired techniques optimized through quantum algorithms. They proposed the Hybrid Grey Wolf Optimizer and Particle Swarm Optimization (HPSOGWO) algorithm for cryptanalysis of the S-AES algorithm.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Further, applying quantum cryptanalysis to block ciphers such as S-DES and S-AES signifies a major advancement, leveraging quantum computing's superior processing capabilities to enhance cryptanalytic efficiency. Rizk-Allah et al [35] demonstrated the power of hybrid algorithms, combining classical and natureinspired techniques optimized through quantum algorithms. They proposed the Hybrid Grey Wolf Optimizer and Particle Swarm Optimization (HPSOGWO) algorithm for cryptanalysis of the S-AES algorithm.…”
Section: Literature Reviewmentioning
confidence: 99%